White Matter Tracts Associated With Deep Brain Stimulation Targets in Major Depressive Disorder: A Systematic Review - Yu, Qun; Guo, Xinxia; Zhu, Zhoule; Feng, Chen; Jiang, Hongjie; Zheng, Zhe; Zhang, Jianmin; Zhu, Junming; Wu, Hemmings (Frontiers in Psychiatry, 2022)
Background Deep brain stimulation (DBS) has been proposed as a last-resort treatment for major depressive disorder (MDD) and has shown potential antidepressant effects in multiple clinical trials. However, the clinical effects of DBS for MDD are inconsistent and suboptimal, with 30–70% responder rates. The currently used DBS targets for MDD are not individualized, which may account for suboptimal effect. Objective We aim to review and summarize currently used DBS targets for MDD and relevant diffusion tensor imaging (DTI) studies. Methods A literature search of the currently used DBS targets for MDD, including clinical trials, case reports and anatomy, was performed. We also performed a literature search on DTI studies in MDD. Results A total of 95 studies are eligible for our review, including 51 DBS studies, and 44 DTI studies. There are 7 brain structures targeted for MDD DBS, and 9 white matter tracts with microstructural abnormalities reported in MDD. These DBS targets modulate different brain regions implicated in distinguished dysfunctional brain circuits, consistent with DTI findings in MDD. Conclusions In this review, we propose a taxonomy of DBS targets for MDD. These results imply that clinical characteristics and white matter tracts abnormalities may serve as valuable supplements in future personalized DBS for MDD.